Service-Dominant Logic Approach to Revisit Intention in Halal Tourism Education: Mediating Roles of Value Co-creation and Perceived Experience - Fitriadi, Budhi Wahyu; Rahayu, Agus; Hendrayati, Heny; Manoarfa, Hilda (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze and test the mediating roles of value co-creation and perceived experience in the relationships between halal tourism attraction, halal tourism literacy, and revisit intention within a Service-Dominant Logic framework. Method: The study employed an explanatory quantitative design involving 270 Muslim tourists who visited halal tourism destinations in Indonesia, selected through purposive and convenience sampling. Data were collected via online questionnaires using a seven-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping procedures. Results: The results demonstrate that both halal tourism attraction and halal tourism literacy exert significant indirect effects on revisit intention through value co-creation and perceived experience as parallel mediators. Serial mediation is also confirmed, where value co-creation precedes perceived experience in sequentially strengthening revisit intention. All measurement models show adequate validity and reliability, with substantial explanatory power (R² ranging from 0.639 to 0.735). Novelty: This study contributes the first integrated model testing both parallel and serial mediation mechanisms simultaneously in halal tourism, positioning value co-creation as an antecedent to perceived experience rather than a competing mediator. The findings offer implications for tourism education curricula, where halal literacy and SDL-based (Service-Dominant Logic) co-creation activities enhance student competencies in Muslim-friendly destination management.